Low-Income, Poor Physical Health, Poor Mental Health, and Other Social Risk Factors Are Associated With Decreased Access to Care in Patients With Carpal Tunnel Syndrome - Sayi P. Boddu; Eugenia Lin; Vikram S. Gill; Nathaniel B. Hinckley; Cara H. Lai; Kevin J. Renfree (SAGE Publishing, 2024)
Background: Carpal Tunnel Syndrome (CTS) is associated with a significant personal and societal burden. Evaluating access to care can identify barriers, limitations, and disparities in the delivery of healthcare services in this population. The purpose of this study was to evaluate access to overall healthcare and healthcare utilization among patients with CTS. Methods: This is a retrospective cohort study conducted with the All of Us database. Patients diagnosed with CTS that completed the access to care survey were included and matched to a control group. The primary outcomes were access to care across 4 domains: (1) delayed care, (2) could not afford care, (3) skipped medications, and (4) over 1 year since seeing provider. Secondary analysis was then performed to identify patient-specific factors associated with reduced access to care. Results: In total, 7649 patients with CTS were included and control matched to 7649 patients without CTS. In the CTS group, 33.7% (n = 2577) had delayed care, 30.4% (n = 2323) could not afford care, 15.4% (n = 1180) skipped medications, and 1.6% (n = 123) had not seen a provider in more than 1 year. Within the CTS cohort, low-income, worse physical health, and worse mental health were associated with poor access to care. Conclusion: Patients experience notable challenges with delayed care, affordability of care, and medication adherence regardless of having a diagnosis of CTS. Targeted interventions on modifiable risk factors such as low income, poor mental health, and poor physical health are important opportunities to improve access to care in this population.